2015
DOI: 10.1186/s12862-015-0431-0
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary analysis of selective constraints identifies ameloblastin (AMBN) as a potential candidate for amelogenesis imperfecta

Abstract: BackgroundAmeloblastin (AMBN) is a phosphorylated, proline/glutamine-rich protein secreted during enamel formation. Previous studies have revealed that this enamel matrix protein was present early in vertebrate evolution and certainly plays important roles during enamel formation although its precise functions remain unclear. We performed evolutionary analyses of AMBN in order to (i) identify residues and motifs important for the protein function, (ii) predict mutations responsible for genetic diseases, and (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 112 publications
7
30
0
Order By: Relevance
“…These genes were not part of the top 95th quantile in the hair Palaeo-Eskimo individual, which instead returned Keratin 17, 32, 33a , Periplaktin , and Plectin , all representing proteins related to hair and hair follicle, in line with findings by Pedersen et al (2014). Unfortunately, we could not investigate genes highly expressed in tooth enamel ( AMELX , TUFT1 , and AMBN) (Delsuc et al 2015) and tooth dentine ( Oc and Dspp ) (Hoffmann et al 2001), as they did not pass our filtering thresholds. Altogether, these analyses plead in favor of the tissue-specificity of R s scores.…”
Section: Resultsmentioning
confidence: 56%
“…These genes were not part of the top 95th quantile in the hair Palaeo-Eskimo individual, which instead returned Keratin 17, 32, 33a , Periplaktin , and Plectin , all representing proteins related to hair and hair follicle, in line with findings by Pedersen et al (2014). Unfortunately, we could not investigate genes highly expressed in tooth enamel ( AMELX , TUFT1 , and AMBN) (Delsuc et al 2015) and tooth dentine ( Oc and Dspp ) (Hoffmann et al 2001), as they did not pass our filtering thresholds. Altogether, these analyses plead in favor of the tissue-specificity of R s scores.…”
Section: Resultsmentioning
confidence: 56%
“…Transcript 1 includes (while transcript 2 omits) a 45 nucleotide segment encoding 15 amino acids at the 5' end of Exon 6 (Cerny et al, ; Hu et al, ). Alignment of 53 functional AMBN sequences, covering over 200 million years (MY) of evolution, identified 80 unchanged and 81 highly conserved amino acid residues (out of 447 residues in the human AMBN protein, inclusive of the signal peptide; Delsuc, Gasse, & Sire, ). All 15 amino acids encoded by the 5'‐end of Exon 6 that can be deleted during RNA splicing are highly or absolutely conserved, and this peptide also includes an O‐glycosylation (human secreted protein Ser 112 ), suggesting that there may be an important functional difference between the two ameloblastin isoforms generated by alternative splicing (Kobayashi et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…All 15 amino acids encoded by the 5'‐end of Exon 6 that can be deleted during RNA splicing are highly or absolutely conserved, and this peptide also includes an O‐glycosylation (human secreted protein Ser 112 ), suggesting that there may be an important functional difference between the two ameloblastin isoforms generated by alternative splicing (Kobayashi et al, ). Evolutionary analysis suggested that ancestral mammalian AMBN likely possessed 11 exons (corresponding to exons 1 to 7 and 10 to 13 in humans, as Exons 8 and 9 were added in the human line by tandem duplications of Exon 7; Delsuc et al, ). All AMBN introns are phase 0 (located between complete codons), so duplication and deletion of exons during evolution, and alternative mRNA splicing, does not shift the downstream reading frame.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the numerous predicted phosphor acceptor sites in AMBN (Toyosawa et al, 2000; Lee et al, 2003), few residues of AMBN have been found to be phosphorylated (reviewed in Delsuc et al, 2015). It is possible that phosphorylation of AMBN is more efficient in vivo , but is effectively removed by alkaline phosphatases before it can be detected.…”
Section: Discussionmentioning
confidence: 99%